Type III interferon exerts thymic stromal lymphopoietin in mediating adaptive antiviral immune response - Cao, Luhong; Qian, Weiwei; Li, Wanlin; Ma, Zhiyue; Xie, Shenglong (Frontiers in Immunology, 2023)
Previously, it was believed that type III interferon (IFN-III) has functions similar to those of type I interferon (IFN-I). However, recently, emerging findings have increasingly indicated the non-redundant role of IFN-III in innate antiviral immune responses. Still, the regulatory activity of IFN-III in adaptive immune response has not been clearly reported yet due to the low expression of IFN-III receptors on most immune cells. In the present study, we reviewed the adjuvant, antiviral, antitumor, and disease-moderating activities of IFN-III in adaptive immunity; moreover, we further elucidated the mechanisms of IFN-III in mediating the adaptive antiviral immune response in a thymic stromal lymphopoietin (TSLP)-dependent manner, a pleiotropic cytokine involved in mucosal adaptive immunity. Research has shown that IFN-III can enhance the antiviral immunogenic response in mouse species by activating germinal center B (GC B) cell responses after stimulating TSLP production by microfold (M) cells, while in human species, TSLP exerts OX40L for regulating GC B cell immune responses, which may also depend on IFN-III. In conclusion, our review highlights the unique role of the IFN-III/TSLP axis in mediating host adaptive immunity, which is mechanically different from IFN-I. Therefore, the IFN-III/TSLP axis may provide novel insights for clinical immunotherapy.